Perancangan Ulang Tata Letak Fasilitas Workshop Fabrikasi Dengan Metode Systematic Layout Planning Di PT ABC - Ahmad Bayu Laksono; Joumil Aidil Saifuddin (Jurnal Kendali Teknik dan Sains, 2023)
PT. ABC is a manufacturing company whose production line is railroad components. In the production process, there is backtracking in the production process so that the production process is less efficient. The purpose of this research is to compare the initial material handling layout mileage with the proposed layout. This study uses the Systematic Layout Planning (SLP) method to determine the layout proposals that will be provided with the help of Blocplan software. From the proposed layout, the total distance traveled for the passenger seat production process is 402.8 meters and at 277.8 meters the difference is 125 meters.